Strong propensity for HIV transmission among men who have sex with men in Vietnam: behavioural data and sexual network modelling. Issue 1 (15th January 2014) - Bengtsson, Linus; Lu, Xin; Liljeros, Fredrik; Thanh, Hoang Huy; Thorson, Anna
Abstract : Objectives: Survey data from men who have sex with men (MSM) in Asian cities indicate ongoing and drastic increases in HIV prevalence. It is unknown which behavioural factors are most important in driving these epidemics. We aimed to analyse detailed sexual behaviour data among MSM in Vietnam and to model HIV transmission using improved assumptions on sexual network structure. Setting: Vietnam. Participants: Internet-using men who had ever had sex (any type) with a man, aged ≥18 years and living in Vietnam. The study was cross-sectional, population-based and performed in 2012, using online respondent-driven sampling. The Internet-based survey instrument was completed by 982 participants, of which 857 were eligible. Questions included sociodemography and retrospective sexual behaviour, including number of unprotected anal sex (UAS) acts per partner. Primary and secondary outcome measures: Estimated basic reproductive number over 3 months as a function of transmission risk per UAS act; frequency distributions of number of UAS partners and UAS acts during last 3 months. Results: 36% (CI 32% to 42%) reported UAS at least once during the last 3 months. 36% (CI 32% to 41%) had ever taken an HIV test and received the result. UAS partner numbers and number of UAS acts were both highly skewed and positively correlated. Using a weighted configuration model, taking into account partner numbers, frequency of UAS and their correlations, we estimated the basic reproductive number (R0) over 3 months. The results indicated rapid transmission over a wide range of values of per-act transmissibility. Conclusions: Men with multiple partners had unexpectedly high UAS frequency per partner, paired with low HIV testing rates. The study highlights the importance of collecting data on frequency of UAS acts and indicates the need to rapidly scale-up HIV prevention services and testing opportunities for MSM in Vietnam.